2021
DOI: 10.3389/fgene.2021.781011
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Support Vector Machine–Based Classifier for Pulmonary Arterial Hypertension Patients

Abstract: Pulmonary arterial hypertension (PAH) is a disease leading to right heart failure and death due to increased pulmonary arterial tension and vascular resistance. So far, PAH has not been fully understood, and current treatments are much limited. Gene expression profiles of healthy people and PAH patients in GSE33463 dataset were analyzed in this study. Then 110 differentially expressed genes (DEGs) were obtained. Afterward, the PPI network based on DEGs was constructed, followed by the analysis of functional mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous studies have also reported the involvement of IFIT2 and IFITM2 in cardiac diseases. IFIT2 has been identified as a potential biomarker of ischemic cardiomyopathy in human and rat heart tissue samples [ 58 ], and it has been found to be highly expressed in HF patients with pulmonary arterial hypertension [ 59 ]. Additionally, studies on rat cardiomyocyte development have suggested that IFITM2 may play a role in differentiation and cell proliferation during cardiac development [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported the involvement of IFIT2 and IFITM2 in cardiac diseases. IFIT2 has been identified as a potential biomarker of ischemic cardiomyopathy in human and rat heart tissue samples [ 58 ], and it has been found to be highly expressed in HF patients with pulmonary arterial hypertension [ 59 ]. Additionally, studies on rat cardiomyocyte development have suggested that IFITM2 may play a role in differentiation and cell proliferation during cardiac development [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…By applying the support vector machine-recursive feature elimination algorithm, our group found that EPB42 and IFIT2 were highly expressed in PAH patients, while FOSB and SNF1LK showed opposite trends. These four potential genes may distinguish PH patients from healthy individuals and can be used for early diagnosis of PH (56). Up to 60% of patients with severe LV systolic insufficiency and 70% of patients with pure LV diastolic insufficiency may develop PH (57,58).…”
Section: Characterization Of Ph In Hfref and Hfpefmentioning
confidence: 99%
“…Machine learning techniques have already found widespread application in the clinical diagnosis of cardiovascular diseases, such as coronary artery calcification scoring. The integration of key mRNAs and traditional diagnostic methods shows promise in enhancing the latter's accuracy [5]. In this study, we obtained gene expression data sets from stroke patients and post-stroke cognitive impairment patients in the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%